MEKANISME INPUT SURVEILANS PNEUMONIA DI DINKES KABUPATEN LAMONGAN TAHUN 2014 - Habibatin Nurul Fajriyah (The Indonesian Journal of Public Health, 2017)
Surveillance pneumonia is a process of regular monitoring against pneumonia and increased risk of pneumonia. The purpose of this study was to determine the input system pneumonia surveillance in Health Office (DHO) Lamongan. Data were obtained from interviews with officers indept holder DHO program pneumonia in Lamongan and reinforced with indept interview to the health center. The pneumonia study conducted by descriptive method and approach that is input surveillance systems that include data sources and types of data, infrastructure, resources and sources of funding. Implementation of a surveillance system in Lamongan district health office is still not well seen from the input that data sources are from the health office health centers, inadequate infrastructure, resources do not meet the needs, and lack of financial resources. Based on the results of research advice given was increased coordination with the health centers, the use of an online system for reporting to the health office, filing budget, quality improvement officer with the holding of training.Keywords: surveillance systems, system input, data sources and types of data, infrastructure, resources, and source of fundszzzz